Development Web-Based Patient Registration and Queue Management System Using RAD Method with QR Code Verification - Samuel Imanuel Hizkia Saraun; Eliasta Ketaren (The IJICS (International Journal of Informatics and Computer Science), 2026)
The smoothness of healthcare services, particularly in the registration and queuing processes, is a key factor influencing patient satisfaction. The Bunda Meifa Foundation Clinic, located in Tondano, faces challenges in patient management due to its manual registration process and dynamic doctor schedules. This research aims to design and build a web-based information system that not only provides a user-friendly self-registration interface for patients but also integrates QR Code verification to expedite the check-in process, reduce waiting times, and ease the workload for staff. The system development method used is Rapid Application Development (RAD), which emphasizes a rapid and adaptive development cycle. The developed system offers modern features such as self-service online registration according to available doctor schedules, the creation of a Digital Card with a unique QR Code as proof of appointment, and an innovative "scan-to-queue" system where queue numbers are assigned upon QR Code scanning at the clinic. For administrators, the system includes a protected dashboard to flexibly manage practice schedules, monitor the queue in real-time, and print queue receipts via a thermal printer. System testing was performed using the Black Box Testing method, and the results indicate that all developed features function as designed. With this system, the registration and queuing processes at the Bunda Meifa Foundation Clinic are expected to become more organized, fair, and structured, ultimately enhancing the overall quality of service.